FATORES DE PERMANÊNCIA NA CARREIRA POLICIAL: UM ESTUDO ENTRE OS PROFISSIONAIS DA GUARDA CIVIL METROPOLITANA DE SÃO PAULO - SILVA, FABIAN DE SOUZA (2017)
The present research studies the factors that motivate the permanence of citizen security officials in a profession that presents a high risk of death for themselves as well for their family, resulting from excessive violence present throughout the national territory, with a cut for this study the Metropolitan Civil Guard from Sao Paulo. It uses a quantitative approach from the following constructs: Career Success Perception Scale; Organizational Entrenchment Scale; Affective Organizational Engagement Scale; and finally, two variables to evaluate the intention to remain in the organization. With descriptive statistics, categorization and correlations, different characteristics were identified between new and experienced police professionals, as well as relationships between the constructs and the intention to remain in the police career. The conclusion can guide management actions in citizen security, especially regarding the commitment and retention of current and future professionals; understanding of the reasons that lead professionals to remain in high-risk occupations, and contribute with research on retention of professionals.